Interventions for treating patients with chikungunya virus infection-related rheumatic and musculoskeletal disorders: A systematic review. - Arturo Martí-Carvajal; Pilar Ramon-Pardo; Emilie Javelle; Fabrice Simon; Sylvain Aldighieri; Hacsi Horvath; Julia Rodriguez-Abreu; Ludovic Reveiz (PLoS ONE, 2017)
Background Chikungunya virus infection (CHIKV) is caused by a mosquito-borne alphavirus. CHIKV causes high fever and painful rheumatic disorders that may persist for years. Because little is known about interventions for treating CHIKV-related illness, we conducted a systematic review. Methods We used Cochrane methods. We searched PubMed, EMBASE, Cochrane Library, LILACS and other sources from the earliest records to March 2016. We had no language restrictions. We included randomized controlled trials assessing any intervention for treating acute or chronic CHIKV-related illness. Our primary outcomes were pain relief, global health status (GHS) or health related quality of life (HRQL), and serious adverse events (SAEs). We assessed bias risk with the Cochrane tool and used GRADE to assess evidence quality. Results We screened 2,229 records and found five small trials with a total of 402 participants. Patients receiving chloroquine (CHQ) had better chronic pain relief than those receiving placebo (relative risk [RR] 2.67, 95% confidence interval [CI] 1.23 to 5.77, N = 54), but acute pain relief was marginally not different between groups (mean difference [MD] 1.46, 95% CI 0.00 to 2.92, N = 54). SAEs were similar (RR = 15.00, 95% CI 0.90 to 250.24, N = 54). Comparing CHQ with paracetamol (PCM), CHQ patients had better pain relief (RR = 1.52, 95% CI 1.20 to 1.93, N = 86). Compared with hydroxychloroquine (HCHQ), disease-modifying anti-rheumatic drugs (DMARDs) reduced pain (MD = -14.80, 95% CI -19.12 to -10.48, N = 72). DMARDs patients had less disability (MD = -0.74, 95% CI -0.92 to -0.56, N = 72) and less disease activity (MD = -1.35; 95% CI -1.70 to -1.00; N = 72). SAEs were similar between DMARDs and HCHQ groups (RR = 2.84, 95% CI 0.12 to 67.53, N = 72). Comparing meloxicam (MXM) with CHQ, there was no difference in pain relief (MD = 0.24, 95% CI = -0.81 to 1.29; p = 0.65, N = 70), GHS or HRQL (MD = -0.31, 95% CI -2.06 to 1.44, N = 70) or SAEs (RR = 0.85, 95% CI 0.30 to 2.42, N = 70). Finally, a four-arm trial (N = 120) compared aceclofenac (ACF) monotherapy to ACF+HCHQ, ACF+ prednisolone (PRD), or ACF+HCHQ+PRD. Investigators found reduced pain (p<0.001) and better HRQL (p<0.001) in the two patient groups receiving PRD, compared to those receiving ACF monotherapy or ACF+HCHQ. Trials were at high risk of bias. GRADE evidence quality for all outcomes was very low. Conclusion Results from these small trials provide insufficient evidence to draw conclusions about the efficacy or safety of CHIKV interventions. Physicians should be cautious in prescribing and policy-makers should be cautious in recommending any intervention reviewed here. Rigorous trials with sufficient statistical power are urgently needed, with results stratified by disease stage and symptomology.